Effect of vitamin D supplementation on markers of vascular function: a systematic review and individual participant meta‐analysis - Beveridge, LA; Khan, F; Struthers, AD; Armitage, J; Barchetta, I; Bressendorff, I; Cavallo, MG; Clarke, R; Dalan, R; Dreyer, G; Gepner, AD; Forouhi, NG; et al. (American Heart Association, 2018)
Background: Low 25‐hydroxyvitamin D levels are associated with an increased risk of cardiovascular events, but the effect of vitamin D supplementation on markers of vascular function associated with major adverse cardiovascular events is unclear. Methods and Results: We conducted a systematic review and individual participant meta‐analysis to examine the effect of vitamin D supplementation on flow‐mediated dilatation of the brachial artery, pulse wave velocity, augmentation index, central blood pressure, microvascular function, and reactive hyperemia index. MEDLINE, CINAHL, EMBASE, Cochrane Central Register of Controlled Trials, and http://www.ClinicalTrials.gov were searched until the end of 2016 without language restrictions. Placebo‐controlled randomized trials of at least 4 weeks duration were included. Individual participant data were sought from investigators on included trials. Trial‐level meta‐analysis was performed using random‐effects models; individual participant meta‐analyses used a 2‐stage analytic strategy, examining effects in prespecified subgroups. 31 trials (2751 participants) were included; 29 trials (2641 participants) contributed data to trial‐level meta‐analysis, and 24 trials (2051 participants) contributed to individual‐participant analyses. Vitamin D3 daily dose equivalents ranged from 900 to 5000 IU; duration was 4 weeks to 12 months. Trial‐level meta‐analysis showed no significant effect of supplementation on macrovascular measures (flow‐mediated dilatation, 0.37% [95% confidence interval, −0.23 to 0.97]; carotid‐femoral pulse wave velocity, 0.00 m/s [95% confidence interval, −0.36 to 0.37]); similar results were obtained from individual participant data. Microvascular function showed a modest improvement in trial‐level data only. No consistent benefit was observed in subgroup analyses or between different vitamin D analogues. Conclusions: Vitamin D supplementation had no significant effect on most markers of vascular function in this analysis. <mods:name type="personal"> <mods:namepart type="given"></mods:namepart> <mods:namepart type="family">Beveridge</mods:namepart> <mods:namepart type="initials">LA</mods:namepart> <mods:displayform>Beveridge, LA</mods:displayform> <mods:role> <mods:roleterm authority="marcrelator" type="text">Author</mods:roleterm> </mods:role> </mods:name> <mods:name type="personal"> <mods:namepart type="given"></mods:namepart> <mods:namepart type="family">Khan</mods:namepart> <mods:namepart type="initials">F</mods:namepart> <mods:displayform>Khan, F</mods:displayform> <mods:role> <mods:roleterm authority="marcrelator" type="text">Author</mods:roleterm> </mods:role> <mods:extension> <mods:identifier type="orcid">0000-0002-9889-0229</mods:identifier> </mods:extension> </mods:name> <mods:name type="personal"> <mods:namepart type="given"></mods:namepart> <mods:namepart type="family">Struthers</mods:namepart> <mods:namepart type="initials">AD</mods:namepart> <mods:displayform>Struthers, AD</mods:displayform> <mods:role> <mods:roleterm authority="marcrelator" type="text">Author</mods:roleterm> </mods:role> </mods:name>